Mapas temáticos da viticultura portuguesa : contribuição para o cadastro dos vinhos portugueses na área de influência da J. N. V. (1942) - Fernandes, Mário Gonçalves (2021)
In Portugal, in the historical cartography of viticulture, there are two important phases in which the use of cartography was recurrent: the first was essentially at the beginning of the last quarter of the nineteenth century, when the surveys and publications of the base cartography were consolidated, until the fall of the monar-chical regime; the second began with the phase of political affirmation of the Estado Novo, and ended in the fifties of the last century. In the context of the sectoral or productive sector corporate bodies created by the Estado Novo, the case of the Junta Nacional do Vinho (1937) is unavoidable. For her, the competences that were previously assigned to the Federaça o dos Viticul-tores do Centro e Sul de Portugal (1933) were transferred. It is precisely from this period that the initiatory example presented and analyzed here is substantiated by the publication in two volumes of the Contribuição para o Cadastro dos Vinhos Portugueses na Área de Influência da J. N. V., whose fieldwork began in 1939 and refers to date of 1942 in the face of both volumes, although it was actually printed in December 1943. This is the survey and analysis of soils, the chemical characteristics of musts, as well as organoleptic conditions, since defective practices in wine production are recurrent, which, in a context of predominance of small producers, would only be partially mitigated by creation, in the 50's, of the network of wineries cooperatives.